2006
DOI: 10.1088/0953-4075/39/19/s31
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic state preparation of a single molecular ion by projection measurement

Abstract: We show how to prepare a single molecular ion in a specific internal quantum state in a situation where the molecule is trapped and sympathetically cooled by an atomic ion and where its internal degrees of freedom are initially in thermal equilibrium with the surroundings. The scheme is based on conditional creation of correlation between the internal state of the molecule and the translational state of the collective motion of the two ions, followed by a projection measurement of this collective mode by atomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…The light fields creating the optical lattice for molecular state detection and spectroscopy are provided by a frequency-doubled dye laser whose frequency is tuned close to the X 1 Σ + (J = 1) → A 1 Σ + (J = 0) transition of 24 MgH + with a variable detuning |∆ MgH | 100 GHz from the molecular transition and detuned by ∆ MgH ≈ 1.5 THz from the atomic D1 transition of 25 Mg + . Two counterpropagating laser beams derived from this laser are linearly polarized in the horizontal plane with a relative detuning δ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light fields creating the optical lattice for molecular state detection and spectroscopy are provided by a frequency-doubled dye laser whose frequency is tuned close to the X 1 Σ + (J = 1) → A 1 Σ + (J = 0) transition of 24 MgH + with a variable detuning |∆ MgH | 100 GHz from the molecular transition and detuned by ∆ MgH ≈ 1.5 THz from the atomic D1 transition of 25 Mg + . Two counterpropagating laser beams derived from this laser are linearly polarized in the horizontal plane with a relative detuning δ.…”
Section: Methodsmentioning
confidence: 99%
“…By tuning the frequency of a laser field near one of the molecular resonances, an ODF is exerted on the molecular ion if it is in one of the states coupled by the corresponding transition. If the strength of this force is oscillating with a frequency close to one of the secular motional frequencies of the two-ion crystal in the trap, it is resonantly enhanced, generating coherent states of motion, which can be detected on a co-trapped atomic ion [23][24][25] . The two lattice beams form a moving interference pattern leading to a temporally and spatially varying light force on both ions.…”
mentioning
confidence: 99%
“…[13,14] it is shown that only 1 collision in 10 4 to 10 6 collisions leads to any internal state relaxation.) We are aware of one other well-developed proposal [16,17] that addresses the need to cool the molecular internal degrees of freedom; however, this method is comparatively very complicated to implement, as it relies on a combination of Raman lasers, spontaneous emission, and black-body radiation to producing rotational cooling, and has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The dem onstrated m otional-ground-state cooling o f a m olecular ion, in particular w hen com bined with cooling at low trap frequency, represents an im portant step towards the im plem entation o f nondestructive state preparation and detection techniques [76][77][78] T he dynam ics o f the system during quasicontinuous SBC is m odeled using optical Bloch equations, w here two electronic states If) and | | ) and 80 trap levels (Fig. 11) are considered.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This is the case for photon recoil spectroscopy [ 11 ] or the nondestructive internal state detection of a molecular ion using oscillating dipole forces [76][77][78]. In the following we extend the single-ion ground-state cooling scheme presented in Sec.…”
Section: Sideband Cooling Beyond the Lamb-dicke Regimementioning
confidence: 99%